Modeling and Testing of Faults in TCAMs - Lee, Kwang-Jin; Kim, Cheol; Kim, Suki; Cho, Uk-Rae; Byun, Hyun-Guen (Systems Modeling and Simulation: Theory and Applications, 2005)
This paper proposes novel fault models for ternary content addressable memories (TCAMs) regarding both physical defects and functional fault models. Novel test algorithms which guarantee high fault coverage and small test length for detecting the faults in high density TCAM cell array is also proposed. The proposed TS − − T algorithm is suitable for detecting physical faults with compact test patterns and provides 92% fault coverage with small test length. Also, the proposed TM − − T algorithm makes it possible to detect various bridging faults among adjacent cells of high density CAMs. The test access time is (10 * l * 3 + 3 ) * write time and (12 * l * 3) * compare time in a n word by l bit TCAM.